(untitled) (Bangladesh Journal of Neuroscience, 2017)
Background: Alzheimer’s disease is a neurodegenerative disease. It is the most common cause of dementia in individuals older than 60 years of age. Age is the most important risk factor for Alzheimer’s disease. It is important to identify modifiable risk factors. One such important modifiable risk factor is Magnesium, a trace element. The objective of the study was to see the association of serum Magnesium concentration with Alzheimer’s disease patients. Method: It was a case control study carried out in neurology department of BSMMU, Dhaka. Total 68 patients were enrolled as study population after satisfying inclusion and exclusion criteria. Among them, 34 were grouped as case and rest 34 were control. Serum Magnesium concentration was detected. Result: Serum Magnesium concentration was significantly lower in AD patients than that of control group [2.04±0.19 mg/dl vs 2.36±0.21 mg/dl. Conclusion: The results of our study revealed an expression that the trace element, Magnesium concentration has an association with Alzheimer’s disease. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 70-75